Resource Allocation for Two-Way Relay Network Based on Cognitive Radio - Shuang Liang; Shouyi Yang; Wanming Hao (Dianxin kexue)
The resource allocation issue for sensing-based spectrum opportunistic access and sensing-based spectrum sharing access in two-way relay cognitive network with imperfect spectrum sensing was discussed.Different from the traditional resource allocation methods for two-way relay network,new algorithm jointly considering sensing time and transmission power in secondary system.Under the condition of the sensing time and the transmission power,the maximal throughput of the secondary system can be obtained.To protect the primary user effectively from interference,the average interference power constraint in each hop was considered.The total transmission power constraint of the secondary system is also considered.The proposed algorithms can acquire the optimal sensing time and power allocation under imperfect spectrum sensing for the sensing-based spectrum opportunistic access and sensing-based spectrum sharing access.Finally,the performance of the two schemes was compared and the effectiveness of the proposed algorithm was verified.